Contributing factors of obesity among stressed adolescents - Tajik, Esra; Mohd Zulkefli, Nor Afiah; Baharom, Anisah; Minhat, Halimatus Sakdiah; Abd Latiff, Latiffah (Electronic Physician, 2014)
Introduction: Many adolescents suffer from common mental disorders such as stress, which affects health through the psychosocial process, eating behavior, food choices and physical activity. During adolescence, dietary patterns are formed and can affect the occurrence of diseases in later life. This is a review of the results in the pertinent literature, from 1989 until November 2013, concerning stress and the contributing factors that lead to obesity among adolescents. The aim of this review is to identify obesity among stressed adolescents as well as the contributing factors. Methods: A descriptive design was used for both quantitative and qualitative studies while, in addition, psychological theories were used for the qualitative studies. The articles were screened to ensure their quality and included in this review accordingly. Ten articles were included in the review comprising cross-sectional, cohort, review and meta-analysis. Interviews and questionnaires were used for data collection. Results: The literature provided obvious information focusing on emotional stress and obesity for both boys and girls. This review revealed that stress results in overweight and obesity among adolescents through changes in lifestyle including decreased physical activity and increased food intake. Gender and economic status are the main components that affect obesity in stressed adolescents. Conclusion: Obesity is a consequence of stress among adolescents and is exacerbated by the wrong eating attitude. Developing proper food choices among adolescents can help prevent obesity and other complications in adulthood.